PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR BIOLOGI PADA MATERI SISTEM REGULASI - Ricky Marojahan Manullang; Ely Djulia (Jurnal Pelita Pendidikan, 2016)
This study aims to determine: (1) The results of studying biology at the material regulatory system students taught by cooperative learning model NHT, (2) Results of studying biology at the material regulatory system students who are taught by the model of expository, and (3) Effect models NHT cooperative learning for learning outcomes on material regulatory systems biology class XI IPA at SMAN 11 Medan TP 2015/2016. Research was conducted on students of class XI IPA at SMAN 11 Medan T.P. 2015/2016. The study population was all students of class XI of five classes (200 people). The sampling technique used by cluster random sampling, so this study sample consisted of two classes each class consists of 40 people. Class experiment with applying cooperative learning model Numbered Heads Together (NHT) and grade control with the application of expository. The findings show: (1) The results of studying biology at the material regulatory system students taught by cooperative learning model NHT has an average value of 81.03 by the tendency of learning outcomes 80% in the high category, (2) Results of studying biology at material regulatory system that taught students with expository teaching model has an average value of 71.40 by the tendency of learning outcomes 72.50% in enough categories, and (3) the influence of cooperative learning model NHT to the learning outcomes on the material systems biology regulation of class XI IPA at SMAN 11 Medan TP 2015/2016. This result is based on the calculation of the difference test average value posttest experimental class and control class obtained that thitung> ttable ie t = 9.22> t table = 1.667.   Keywords: Numbered Heads Together (NHT), Learning Outcomes